Manajemen Sarana dan Prasarana Perspektif Al-Qur’an dan Hadist - Samsul Arifin; Afriza Afriz; Tuti Andriani (Dinasti Review, 2022)
Abstract: The purpose of this article is to examine the contextual values of real estate and infrastructure management from the perspective of Al-Hadith and the Koran, by considering the design, operation, inventory, and monitoring of facilities and infrastructure components. The method used is the maudhu interpretation method (thematic. The first result, the context of management of facilities and infrastructure, becomes effective and efficient. Second, planning the interpretation of verse 18 sura al-Hasyr (59) so that each plans his future formulated as an understanding of the implementation of actions. Third, using the interpretation of Surah An-Nahl (16) verses 5-8, everyone can maximize all the potential of existing resources, both human and natural, as efficiently and effectively as possible. Fourth, a list of interpretations of surahs Al-Baqarah (2) verse 282 concerning the urgency of recording so that it is easier to learn and become textual information when school institutions are responsible Fifth, supervision of the interpretation of 7 verses of Surah Al-Mujaadillah (58) is necessary to avoid deviations both in reporting, performance, and results. Abstrak: Tujuan artikel ini adalah untuk mengkaji nilai-nilai kontekstual manajemen real estat dan infrastruktur dari perspektif Al-Hadits dan Alquran, dengan mempertimbangkan desain, pengoperasian, inventarisasi, dan pemantauan komponen sarana dan prasarana. Metode yang digunakan adalah metode tafsir maudhu (tematik. Hasil pertama, konteks pengelolaan sarana dan prasarana, menjadi efektif dan efisien. Kedua, merencanakan tafsir ayat 18 surat al-Hasyr (59) agar setiap individu merencanakan persiapan masa depannya sedemikian rupa sehingga apa yang dilakukan dirumuskan sebagai pemahaman tentang pelaksanaan perbuatan. Ketiga, menggunakan tafsir surat An-Nahl (16) ayat 5-8, bahwa setiap orang dapat memaksimalkan segala potensi sumber daya yang ada, baik manusia maupun alam, seefisien dan seefektif mungkin. Keempat, daftar tafsir surat Al-Baqarah (2) ayat 282 tentang urgensi pencatatan agar lebih mudah dipelajari dan menjadi informasi tekstual ketika lembaga sekolah bertanggung jawab. Kelima, pengawasan terhadap tafsir 7 ayat Surah Al-Mujaadillah (58) mutlak diperlukan untuk menghindari penyimpangan baik dalam pemberitaan, kinerja maupun hasil.